EFL LEARNERS’ SELF-REGULATION SKILLS IN TECHNOLOGY-ENHANCED FACTUAL AND CRITICAL WRITING - Fitriati, Sri Wuli; Wijayatiningsih, Testiana Deni; Farida, Alief Noor; Hapsari, Christianti Tri (Journal of English Education Program, 2026)
This study aimed to examine how EFL learners' self-regulation skills manifest during technology-enhanced factual and critical writing. This study combined platforms such as WhatsApp, Zoom meetings, and e-learning to explore students' metacognition, self-concept, self-monitoring, motivation, and strategy formation in writing factual and critical texts. Employing a descriptive approach, this study used a five-point Likert-scale questionnaire to investigate 35 EFL students' self-regulation during writing. A genre-based approach was implemented in class to improve students' self-regulation skills in four stages: creating and activating prior information, talking, modelling, memorizing, supporting, and independent performance. This study found that students' self-regulation of factual and critical writing showed metacognition through preparation, goal setting, and reducing disruptions. Second, critical thinking and learning styles revealed the students' self-concept. Self-monitoring was observed based on students' awareness, activities, and self-management. Students were motivated in terms of driving, willingness, and self-confidence in writing skills. Finally, students' strategy formation involves topic knowledge, student needs analysis, searchability evaluation, feedback, idea generation, writing initiation, outlining, drafting, revision before submission, and proofreading. Self-regulation in factual and critical writing was achieved through staged activities: material activation, interaction, modelling, memorization, support, and independent performance, leading students to cognitive and affective mastery in critical writing. In conclusion, this study confirms that students' success in factual and critical writing is closely linked to their self-regulation. These findings imply that writing instruction should explicitly scaffold self-regulation through sequential activities, as presented in this study.